The repertoire in the identity construction of wind bands (Orfeu, 2021)
The plurality of customs and values ​​present in wind bands is a characteristic discussed in a wide bibliography on the subject. The identity construction of these musical groups has been taking place from their interactions with different segments of society, always permeated by their repertoire. We present in this text a discussion about these interactions of the bands whose background is the presence of the repertoire in these interactions. The main objective is to discuss the role of the repertoire in the identity construction of the band movement in Brazil. We started from the episodes of the master's research fieldwork completed in 2019. Similar situations from different regions and historical moments are placed in dialogue with the observed episodes. The theoretical perspective adopted is based on the conception of music as a language based on the philosophy of Bakhtin's circle. From this we observe that the bands repertoire is built on the same dynamics of the development of the groups and plays different roles in an extensive historical plot of musical meanings.
Keywords: Wind Band; Repertoire; Identity Construction